Perfect match [compact disc, unabridged] - Michaels, Fern (Brilliance Audio, 2015)
NFL star Jake Masters has a spinal injury that ended his career. Now confined to a wheelchair, unwilling to take a chance on another risky surgery that could restore his mobility. But his twin sister, Beth, has no intention of letting him languish there forever, and she's gifting a matchmaking business to Jake; whether he likes it or not. It's soon clear that he needs an assistant. Enter Gracie Sweet, whose slender frame belies a take-no-charge toughness that would put any linebacker to shame.